RESEARCH AND DEVELOPMENT (R&D) AND FIRM VALUE: AN EMPIRICAL STUDY FROM NON FINANCIAL SECTOR FIRM IN THE ERA OF MODERN TECHNOLOGY - Edi Pranyoto; Susanti Susanti; Rubi Maulana Muis (Proceeding International Conference on Information Technology and Business, 2019)
The purpose of this study was to determine the positive influence of Research and Development (RD ) on firm value. The results show that RD does not have a significant effect on firm value, while Corporate Social Responsibility (CSR) and type of industry have a significant impact on firm value. RD activities are activities that will be the company's investment in the long run. RD activities create a competitive advantage for companies by creating new products that are difficult for competitors to emulate in the era of modern technological development. Companies that carry out RD activities in the era of modern technology can be considered to have made long-term strategic investment companies that are used to increase firm value. Investors did not invest because RD is a strategic investment in the long term of the company that is used to increase the value of the company, while technology is developing very rapidly.Keywords: Research and Development, firm value, modern technology